Importancia de la característica cualitativa fundamental representación fiel para la preparación de los estados financieros bajo NIIF. - Flores Mosquera, Julissa Shayri (My University, 2022)
In order for managers, partners, investors, creditors and users to be able to make better decisions in their organization, it is important for them to know the situation in which they really find themselves. Therefore, it is essential to understand the qualitative characteristics of the financial information provided by the Conceptual Framework of the accounting standards in force, especially, for this research, the fundamental qualitative characteristic of faithful representation, since these are conditions processed in the different standards, which allow reflecting in the financial statements reliable, effective and interpretable values and information. The objective is to analyze the fundamental qualitative characteristic "faithful representation" of financial information, by means of a practical case study, with the purpose of demonstrating the importance of its application in the presentation of financial statements for correct decision making. In order to achieve this objective, the implementation of a research-bibliographic methodology is considered necessary, since scientific articles, different works related to the subject matter and complementary documents that served as a theoretical construct were investigated, while the level applied for the research is descriptive with a qualitative approach.
Para que gerentes, socios, inversionistas, acreedores y usuarios puedan tomar decisiones más acertadas en su organización, es considerable que conozcan la situación en la que verdaderamente se encuentra, por ello, es fundamental comprender las características cualitativas de la información financiera que brinda el Marco Conceptual de las normas contables vigentes, sobre todo, para esta investigación, la característica cualitativa fundamental de representación fiel, puesto que, son condiciones procesadas en los diferentes estándares, que permiten reflejar en los estados financieros valores e información confiable, eficaz y posibles de interpretar. Se plantea como objetivo analizar la característica cualitativa fundamental “representación fiel” de la información financiera, mediante el planteamiento de un caso práctico, con la finalidad de demostrar la importancia que tiene la aplicación de la misma en la presentación de los estados financieros para una correcta toma de decisiones. A efecto de alcanzar dicho objetivo, se considera necesaria la implementación de una metodología investigativa-bibliográfica, ya que se indagó en artículos científicos, en distintos trabajos que guardan relación a la temática y en documentos complementarios que sirvieron como constructo teórico, mientras que el nivel aplicado para la investigación es el descriptivo con un enfoque cualitativo.
Keywords: REPRESENTACIÓN FIEL; INFORMACIÓN FINANCIERA; ESTADOS FINANCIEROS; TOMA DE DECISIONES